The role of pre- operative wire localisation of occult lesions for early detection of breast cancer. - Nikolova, Sonja (My University, 2012)
An increasing number of non-palpable breast lesions are being detected due to the widespread use of screening mammography in asymptomatic women. The sensitivity of the first screening mammogram increases with age. The ability of mammography to differentiate malignant lesions from benign ones is quite variable, where 9%–63% of all reported mammographic abnormalities are eventually diagnosed as malignant. Needle localisation open breast biopsy was first introduced in 1965 in order to obtain a histological diagnosis of such lesions. The placement of the radio-opaque wire percutaneously into the lesion, under the guidance of either a mammogram or an ultrasonography, is done preoperatively by the radiologist. The rationale for this is that the wire guides the surgeon to the exact site of the lesion and hence avoids the removal of an unnecessarily large volume of breast tissue. In this audit, we examined our institution’s experience with performing hookwire localisation biopsy for mammogram-detected lesions that were classified as suspicious breast lesions such as non-palpable breast mass or clustered microcalcifications, that require accurate diagnosis to achieve early detection of cancer. Complete removal of the lesion associated with radiological study of the specimen appears to be critical to avoid false negative findings and to provide precise histopathologic diagnosis. The aim of the study was to evaluate our experience with an original method of wire localisation followed by excisional biopsy for occult breast lesions and to proove the usefulness of preoperative hooked-wire localization of such lesions for the early detection of breast cancer.
Keywords: Neoplasia; Calcifications / Calculi; Localisation; Ultrasound; Mammography; Breast